2001
DOI: 10.1136/gut.48.4.468
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal COX-2 expression in human myenteric plexus in active inflammatory bowel disease

Abstract: Background-Inflammatory bowel disease (IBD) is associated with changes in colonic motility which may contribute to the pain and diarrhoea associated with exacerbations of this disease. These changes may be mediated by prostaglandins which are increased in this condition. Increased expression of the inducible isoform of cyclo-oxygenase (COX-2) has been found in active IBD although its cellular distribution remains uncertain. Aims-To evaluate the cellular distribution of COX-2 in active IBD. Patients and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 23 publications
(20 reference statements)
3
55
0
1
Order By: Relevance
“…, whereas other authors reported a scarce or absent expression (Roberts et al, 2001;Schwarz et al, 2001).…”
mentioning
confidence: 39%
“…, whereas other authors reported a scarce or absent expression (Roberts et al, 2001;Schwarz et al, 2001).…”
mentioning
confidence: 39%
“…In addition, UC samples used in this study did not show detectable p53 serine 46 phosphorylation, a modification involved in p53-mediated apoptosis (40). Because macrophage migration inhibitory factor (MIF) can inhibit p53-mediated apoptosis (41,42), possibly through PGE-2 production by COX-2 (41,43), and levels of MIF are increased in UC when compared with normal colon samples (44,45), free radical-damaged cells could escape apoptosis and clonally expand. In addition, NO can further attenuate apoptosis by directly inhibiting caspases via nitrosylation (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Given that much of the morbidity associated with inflammatory bowel disease is caused by disordered gastrointestinal motor function and that colonic smooth muscle function is regulated by the ENS, it is quite possible that alterations in the excitability of the enteric neurons contribute to intestinal dysmotility. A variety of immune-mediated inflammatory disorders exist, including Crohn's disease and ulcerative colitis, and dysmotility, hypersecretion, and enhanced perception of pain are common features (17,22,23,46). It is now clear that cutaneous and visceral inflammations lead to enhanced excitability of extrinsic primary afferent neurons and altered reflex activity (5,8,14,48).…”
mentioning
confidence: 99%
“…A common feature of intestinal inflammation is the upregulation of the cyclooxygenase-2 (COX-2) enzyme, leading to increased synthesis of several eicosanoids (16,46,47,50), including prostaglandin E2 (PGE 2 ). Within guinea pig submucosal plexus neurons in the colon, PGE 2 application has been shown to lead to membrane depolarization and increased action potential frequency, as well as increased chloride ion secretion (18).…”
mentioning
confidence: 99%